Strategy to Make JSPM’S ICOER A – Building Carbon Neutral: Approaches towards Achieving Carbon Neutral Status in Higher Education Institutions (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Climate change is the most serious challenges the world is facing. Addressing this challenge is a shared responsibility of all governments, universities, businesses and other wider community. All across the world, colleges and universities are trying to become Carbon Neutral. To become Carbon Neutral, universities are working to reduce their Greenhouse gases emissions, cut their use of energy, use more renewable energy and emphasize the importance of sustainable energy sources.